Dehydrochlorination catalyst, preparation method and application thereof in synthesis of 1, 1, 2-trichloroethylene from 1, 1, 2, 2-tetrachloroethane
By pretreating and pore-forming activated carbon and reacting with metal salts, an efficient dehydrogenation catalyst is prepared, which solves the problems of low catalytic activity and stability in the prior art, and achieves efficient catalytic performance and long life in the preparation reaction of trichloroethylene.
Patent Information
- Application Number
- CN202510126440.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-27
AI Technical Summary
The existing preparation methods for trichloroethylene have problems such as limited raw material sources, difficulty in treating three wastes, and low catalytic activity and stability.
An efficient dehydrogen chloride catalyst was prepared by pretreating the activated carbon support with acid or alkali, pore formation, and immersing with the metal brine solution, lyophilizing and lyophilizing, and then reducing and chlorinating.
The activity and stability of the catalyst are improved, the catalytic performance in the synthesis of trichloroethylene in 1,1,2,2-tetrachloroethane dehydrogenation and the service life of the catalyst is extended.
Smart Images

Figure BDA0005260018570000191 
Figure BDA0005260018570000201
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic synthesis, and specifically relates to a dehydrochlorination catalyst and a preparation method thereof, and application of the catalyst in synthesizing 1,1,2-trichloroethylene from 1,1,2,2-tetrachloroethane. Background Art
[0002] Trichloroethylene is widely used in refrigerant raw materials, cleaning agents, chemical intermediates, etc. Secondly, it is also an excellent organic chlorine solvent, widely used in precision machinery, microelectronics, chemical and pharmaceutical industries. Chloroolefins are one of the important routes for realizing large-scale conversion of C-Cl to CF to synthesize fluoroalkanes. With the ban of chloroalkanes, a refrigerant that destroys the ozone layer in recent years, the demand for their substitutes, such as fluoroalkanes, has grown rapidly. Therefore, the application prospects of trichloroethylene are becoming more and more broad.
[0003] At present, the main method for producing trichloroethylene is the acetylene-saponification method. This method uses carbide acetylene as raw material and solid ferric chloride as catalyst. Under negative pressure conditions, the molar ratio of acetylene to chlorine is 1:1.01, the temperature is 90-130°C, and liquid phase chlorination is carried out in a chlorination tower to obtain tetrachloroethane. The tetrachloroethane and lime are saponified at a mass ratio of 1:1.45 at 80-100°C to produce trichloroethylene, and then the finished product is obtained by crude distillation and rectification. However, due to the limited raw material source and the difficulty in treating the three wastes, this preparation method has been gradually eliminated.
[0004] In addition, the oxychlorination of dichloroethane is also one of the more common methods. However, the preparation method has a complex reaction and the process is difficult to control. Therefore, it has not been widely used in industrial production. The gas-phase catalytic dehydrochlorination of tetrachloroethane has the characteristics of low reaction temperature, less three wastes, and simple process, and has gradually become the mainstream process of industrial production. At present, the most studied dehydrochlorination catalyst is activated carbon or activated carbon-supported metal sulfate / BaCl2 catalyst.
[0005] The invention with the publication number CN101032690 discloses a high-activity catalyst for preparing chloroolefins by gas-phase catalytic dehydrochlorination of chloroalkanes and a preparation method thereof, wherein activated carbon is pretreated under high temperature conditions, and then an active component alkali metal sulfate (Na2SO4, K2SO4, etc.) is impregnated onto the activated carbon treated at high temperature, and then dried at 110-140°C for 6 hours to obtain a catalyst, which is applied to the reaction of preparing chloroolefins by gas-phase catalytic dehydrochlorination of chloroalkanes, and has high catalytic activity, a high conversion rate of the raw materials, and high stability of the catalyst. However, existing studies have shown that these types of catalysts still have the problems of poor catalytic activity and low stability. Summary of the invention
[0006] In order to solve the problems of raw material source, three wastes treatment and low activity in the acetylene-saponification preparation process, the present invention provides a dehydrochlorination catalyst and a preparation method thereof and application in the synthesis of 1,1,2-trichloroethylene from 1,1,2,2-tetrachloroethane.
[0007] In a first aspect, the present invention provides a method for preparing a dehydrochlorination catalyst, comprising the following steps:
[0008] A1. Add activated carbon to 5-10wt% HNO3 solution or 5-10wt% NH3·H2O solution and reflux at a reflux temperature of 50-80°C for 5-10h; after reflux, wait for the temperature to drop to room temperature, filter with deionized water and wash to neutral, and dry to obtain pre-treated activated carbon;
[0009] A2. Add a pore-forming agent to the activated carbon, let it stand for 2-6 hours, transfer it to a tube furnace, and heat it to 400-800°C at a rate of 1-10°C / min under an inert atmosphere, with a gas flow rate of 20-60mL / min, and maintain it for 2-8 hours; the pore-forming agent is one of water, polyethylene glycol, polyvinyl alcohol, and polyacrylamide, or a combination of water and any one of polyethylene glycol, polyvinyl alcohol, and polyacrylamide;
[0010] A3. Prepare a metal salt aqueous solution, wherein the solute in the metal salt solution is one of Zn(NO3)2, Ba(NO3)2 and CsNO3 or a combination of Zn(NO3)2 and one of Ba(NO3)2 and CsNO3, add the activated carbon obtained in A2 thereto, and immerse at room temperature for 5-10 hours to obtain a product; then, freeze-dry to obtain a product; the mass ratio of the activated carbon to the metal salt is 10-40:1;
[0011] A4. The product in A3 is placed in a tubular furnace, and a reducing gas containing hydrogen is introduced to reduce the metal salt to a metal element. The reduction conditions are: heating to 300-800°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and maintaining the temperature for 2-5h; then HCl gas is introduced to react with the metal element to generate a metal chloride. The reaction conditions are: introducing HCl gas at a gas flow rate of 20-60mL / min, and reacting at room temperature to 800°C for 0.1-3h, thereby obtaining a dehydrochlorination catalyst.
[0012] Preferably, the activated carbon in step A1 is one of wood carbon and coconut shell carbon.
[0013] Preferably, in step A1, the feed ratio of activated carbon to HNO3 solution or NH3·H2O solution is 1 g: 20-50 mL.
[0014] Preferably, the mass ratio of activated carbon to pore-forming agent in step A2 is 1:2-4.
[0015] Preferably, the inert atmosphere in step A2 is one of nitrogen, argon and helium.
[0016] As a preferred embodiment, after the treatment in step A2, the activated carbon is mainly microporous, the micropore ratio is greater than 90%, and the specific surface area is 800-1000m 2 / g, an average pore diameter of 1.0nm to 1.5nm, and the amount of oxygen-containing functional groups on the surface is between 0 and 1.0wt% in terms of oxygen content.
[0017] Preferably, in step A3, the metal salt is a combination of Zn(NO3)2 and one of Ba(NO3)2 and CsNO3, wherein the mass ratio of Zn(NO3)2 to one of Ba(NO3)2 and CsNO3 is 1:0.5-1.5.
[0018] Preferably, the freeze-drying conditions in step A3 are: freeze-drying the impregnated product at -30 to -50°C for 20 to 30 hours.
[0019] In step A4 of the present invention, the reducing gas containing hydrogen is preferably a H2 / Ar mixed gas, wherein the volume percentage content of hydrogen is 5-10%, more preferably 5%.
[0020] The reduction conditions in step A4 of the present invention are determined according to the metal. When the metal is Zn, the reduction conditions are preferably: heating to 300-400°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and maintaining the temperature for 2-5h. When the metal is one of Ba and Cs3 or a combination of Zn and one of Ba and Cs, the reduction conditions are preferably: heating to 300-400°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and maintaining the temperature for 1-3h; then, heating to 400-800°C at a rate of 1-10°C / min, and maintaining the temperature for 1-3h.
[0021] The reaction temperature of HCl gas and metal element in step A4 of the present invention is also determined according to the metal. When the metal is Cs or a combination of Zn and Cs, the reaction conditions for generating metal chloride are preferably: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature for 0.1 to 3 hours. When the metal is Zn or a combination of Zn and Ba, the reaction conditions for generating metal chloride are preferably: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature for 0.1 to 1 hour, then heating to 400-800°C at a rate of 1-10°C / min, and then maintaining for 0.1-1 hour. When the metal is Ba, the reaction conditions for generating metal chloride are preferably: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature, heating to 400-800°C at a rate of 1-10°C / min, and then maintaining for 0.1-1 hour.
[0022] In a second aspect, the present invention provides a dehydrochlorination catalyst prepared according to the preparation method described in the first aspect. The dehydrochlorination catalyst is composed of a carrier and an active component supported on the carrier, wherein the carrier is activated carbon; and the active component includes a metal chloride.
[0023] In a third aspect, the present invention proposes the use of the dehydrochlorination catalyst described in the second aspect in the synthesis of 1,1,2-trichloroethylene from 1,1,2,2-tetrachloroethane.
[0024] The steps of the application are as follows:
[0025] B1. Fill a proper amount of quartz wool in the reaction tube, weigh a certain mass of dehydrochlorination catalyst and fill it into the reaction tube padded with quartz wool, the particle size ratio of the reaction tube to the catalyst is 10-20, then raise the temperature of the reaction tube to 150-250℃, after the temperature stabilizes, use nitrogen or argon as carrier gas to bring the vaporized 1,1,2,2-tetrachloroethane into the reactor, the carrier gas flow rate is 20-60mL / min, the raw material feed space velocity is 7000-15000h -1 .
[0026] B2. The product enters the gas-liquid separator after passing through the condensation device. The liquid product is collected and diluted after condensation and analyzed by Agilent gas chromatography. The gas product HCl is absorbed by alkaline solution.
[0027] The beneficial effects of the present invention are:
[0028] 1. The activated carbon carrier is pre-treated with acid or alkali to enhance or weaken the acidity of the carrier surface, which is beneficial to the improvement of catalyst activity. In addition, the oxygen-containing functional groups on the catalyst surface are effectively reduced, and the concentration of oxygen-containing functional groups is lower, which is more conducive to the improvement of catalytic activity. At the same time, after pore-forming treatment, the specific surface area, pore volume and pore size of the carrier are increased, which is beneficial to the improvement of catalyst activity.
[0029] 2. During the catalyst preparation process, the activated carbon is directly impregnated with the active component and the catalyst is dried by freeze drying, thus avoiding the problem of the active component being lost with the evaporation of deionized water during heating and drying.
[0030] 3. The dehydrochlorination catalyst of the present invention has good catalytic activity in the dehydrochlorination reaction of 1,1,2,2-tetrachloroethane to synthesize trichloroethylene, and can maintain high conversion rate and selectivity after long-term use. DETAILED DESCRIPTION
[0031] The following examples are only used to further illustrate the present invention, but the protection scope of the present invention is not limited thereto.
[0032] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0033] The activated carbon used in the examples was purchased from Wenzhou Feiruide Trading Co., Ltd., model number 3SW.
[0034] Example 1
[0035] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0036] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0037] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and immerse it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0038] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0039] Example 2
[0040] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0041] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.8wt% (based on O content) as determined by VarioEL analyzer.
[0042] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and immerse it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0043] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0044] Example 3
[0045] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0046] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 96% and the specific surface area is 950m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0047] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0048] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0049] Example 4
[0050] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0051] Step 2: Removal of oxygen-containing groups: Add 20g of polyvinyl alcohol to the treated activated carbon, let it stand for 2h, transfer it to a tube furnace, heat it to 350℃ at a rate of 1℃ / min under nitrogen atmosphere, keep it for 2h, and continue to heat it to 600℃ and keep it for 4h. According to BET characterization analysis, the micropore ratio is 94% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0052] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0053] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0054] Example 5
[0055] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0056] Step 2: Removal of oxygen-containing groups: Add 10 mL of water and 10 g of polyvinyl alcohol to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600 ° C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0057] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0058] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0059] Example 6
[0060] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0061] Step 2: Removal of oxygen-containing groups: Add 10 mL of water and 10 g of polyacrylamide to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600 ° C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 860m 2 / g, the average pore size is 1.0nm, and the number of oxygen-containing groups on the surface is 0.2wt% (calculated as O content) as determined by VarioEL analyzer.
[0062] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0063] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0064] Example 7
[0065] Step 1: Activated carbon pretreatment: 10 g activated carbon was added to 300 mL 10 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 3, that is, the number of weakly acidic sites increased.
[0066] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 10°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 90% and the specific surface area is 800m 2 / g, the average pore diameter is 1.2nm, and the number of oxygen-containing groups on the surface is 0.1wt% (based on O content) as determined by VarioEL analyzer.
[0067] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0068] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 5°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0069] Example 8
[0070] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0071] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0072] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then immerse 5g activated carbon in it, immerse it at room temperature for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0073] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min in a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and after it was cooled to room temperature, HCl gas was passed into it and maintained for 1 h. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 h, and naturally cooled to room temperature.
[0074] Example 9
[0075] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0076] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0077] Step 3: Loading of active components: Take 0.250g Ba(NO3)2 in a beaker, add 10mL water, and after the solid is completely dissolved, 5g activated carbon is immersed in it. The product is immersed at room temperature for 5h to obtain the product, and then freeze-dried at -50℃ for 24h to obtain the product.
[0078] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was introduced therein, and the temperature was raised to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0079] Example 10
[0080] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0081] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 91% and the specific surface area is 900m 2 / g, the average pore diameter is 1.0nm, and the number of oxygen-containing groups on the surface is 0.8wt% (calculated as O content) as determined by VarioEL analyzer.
[0082] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then immerse 5g activated carbon in it, immerse it at room temperature for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0083] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min in a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and after it was cooled to room temperature, HCl gas was passed into it and maintained for 1 h. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 h, and naturally cooled to room temperature.
[0084] Embodiment 11
[0085] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0086] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.8wt% (based on O content) as determined by VarioEL analyzer.
[0087] Step 3: Loading of active components: Take 0.250g Ba(NO3)2 in a beaker, add 10mL water, and after the solid is completely dissolved, 5g activated carbon is immersed in it. The product is immersed at room temperature for 5h to obtain the product, and then freeze-dried at -50℃ for 24h to obtain the product.
[0088] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was introduced therein, and the temperature was raised to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0089] Example 12
[0090] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0091] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0092] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0093] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0094] Example 13
[0095] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0096] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 91% and the specific surface area is 900m 2 / g, the average pore diameter is 1.0nm, and the number of oxygen-containing groups on the surface is 0.8wt% (calculated as O content) as determined by VarioEL analyzer.
[0097] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0098] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0099] Embodiment 14
[0100] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0101] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 850m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0102] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g CsNO3 therein, and then impregnate 5g activated carbon therein, and immerse it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0103] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0104] Embodiment 15
[0105] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0106] Step 2: Removal of oxygen-containing groups: Add 20g of polyvinyl alcohol to the treated activated carbon, let it stand for 2h, transfer it to a tube furnace, heat it to 350℃ at a rate of 1℃ / min under nitrogen atmosphere, keep it for 2h, and continue to heat it to 600℃ and keep it for 4h. According to BET characterization analysis, the micropore ratio is 94% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0107] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0108] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0109] Example 16
[0110] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0111] Step 2: Removal of oxygen-containing groups: Add 10 mL of water and 10 g of polyvinyl alcohol to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600 ° C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.2wt% (based on O content) as determined by VarioEL analyzer.
[0112] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0113] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0114] Embodiment 17
[0115] Step 1: activated carbon pretreatment: 10 g activated carbon was added to 300 mL 7.5 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 1, that is, the number of weakly acidic sites increased.
[0116] Step 2: Removal of oxygen-containing groups: Add 10 mL of water and 10 g of polyacrylamide to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600 ° C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 860m 2 / g, the average pore size is 1.0nm, and the number of oxygen-containing groups on the surface is 0.2wt% (calculated as O content) as determined by VarioEL analyzer.
[0117] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0118] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0119] Embodiment 18
[0120] Step 1: Activated carbon pretreatment: 10 g activated carbon was added to 300 mL 10 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 3, that is, the number of weakly acidic sites increased.
[0121] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 10°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 90% and the specific surface area is 800m 2 / g, the average pore diameter is 1.2nm, and the number of oxygen-containing groups on the surface is 0.1wt% (based on O content) as determined by VarioEL analyzer.
[0122] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.250g CsNO3 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0123] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0124] Embodiment 19
[0125] Step 1: Activated carbon pretreatment: 10 g activated carbon was added to 300 mL 10 wt% NH3·H2O solution and refluxed at 50°C for 10 h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100°C for 24 h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of the activated carbon. The NH3 desorption peak area of the activated carbon at low temperature after alkali pretreatment was larger than that in Example 3, that is, the number of weakly acidic sites increased.
[0126] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 90% and the specific surface area is 900m 2 / g, the average pore diameter is 1.2nm, and the number of oxygen-containing groups on the surface is 0.1wt% (based on O content) as determined by VarioEL analyzer.
[0127] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then immerse 5g activated carbon in it, immerse it at room temperature for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0128] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min in a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and after it was cooled to room temperature, HCl gas was passed into it and maintained for 1 h. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 h, and naturally cooled to room temperature.
[0129] Embodiment 20
[0130] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0131] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0132] Step 3: Loading of active components: Take 0.250g CsNO3 in a beaker, add 10mL water, and after the solid is completely dissolved, 5g activated carbon is immersed in it. The product is immersed at room temperature for 5h to obtain the product, and then freeze-dried at -50℃ for 24h to obtain the product.
[0133] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0134] Embodiment 21
[0135] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0136] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 5°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.8wt% (based on O content) as determined by VarioEL analyzer.
[0137] Step 3: Loading of active components: Take 0.250g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then immerse 5g activated carbon in it, immerse it at room temperature for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0138] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min in a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and after it was cooled to room temperature, HCl gas was passed into it and maintained for 1 h. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 h, and naturally cooled to room temperature.
[0139] Embodiment 22
[0140] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% HNO3 solution and refluxed at 50℃ for 10h. After the reflux, the temperature was cooled to room temperature, filtered with deionized water and washed to neutrality, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After acid pretreatment, a new NH3 desorption peak appeared at 200-250℃, that is, the number of strong acid sites increased.
[0141] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 93% and the specific surface area is 930m 2 / g, the average pore diameter is 1.3nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0142] Step 3: Loading of active components: Take 0.250g CsNO3 in a beaker, add 10mL water, and after the solid is completely dissolved, 5g activated carbon is immersed in it. The product is immersed at room temperature for 5h to obtain the product, and then freeze-dried at -50℃ for 24h to obtain the product.
[0143] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 h, and then heated to 400°C at a rate of 1°C / min, maintained for 2 h. After it was cooled to room temperature, HCl gas was passed into it, maintained for 1 h, and naturally cooled to room temperature.
[0144] Comparative Example 1
[0145] Compared with Example 1, Comparative Example 1 differs in that the activated carbon does not remove oxygen-containing groups nor undergo pore-forming treatment, and the remaining treatment methods are exactly the same as those of Example 1.
[0146] Step 1: Activated carbon pretreatment: Add 10g activated carbon to 300mL 5wt% NH3·H2O solution and reflux at 50℃ for 10h. After reflux, wait for the temperature to drop to room temperature, filter with deionized water and wash with water until neutral, dry at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weak acid sites increased. According to BET characterization analysis, the micropore ratio is 88% and the specific surface area is 600m 2 / g, the average pore diameter is 0.6nm, and the number of oxygen-containing groups on the surface is 1.5wt% (based on O content) as determined by VarioEL analyzer.
[0147] Step 2: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, and impregnate it at room temperature for 5h to obtain the product. Subsequently, freeze-dry it at -50℃ for 24h to obtain the product.
[0148] Step 3: Reduction and chlorination of active components: The product in step 3 was moved to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after it was cooled to room temperature, HCl gas was passed into it and maintained for 1 hour, then, heated to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0149] Comparative Example 2
[0150] The difference between Comparative Example 2 and Example 1 is that the active component is not chlorinated, and the rest of the treatment is exactly the same as that of Example 1.
[0151] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0152] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to 10 g of activated carbon, let stand for 2 h, transfer to a tube furnace, heat to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep for 2 h, and continue to heat to 600 ° C and keep for 4 h. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940 m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0153] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g CsNO3 therein, and then immerse 5g activated carbon therein, immerse for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0154] Step 4: Reduction of active components: Move the product in step 3 to a tubular furnace and heat it to 300°C at a rate of 1°C / min in a hydrogen-argon mixture (5% H2+95% Ar), maintain it for 2 hours, then heat it to 400°C at a rate of 1°C / min, maintain it for 2 hours, and naturally cool it to room temperature.
[0155] Comparative Example 3
[0156] Compared with Example 1, Comparative Example 3 differs in that the drying method is changed to a blast drying oven for drying, and the other processing methods are exactly the same as those of Example 1.
[0157] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0158] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated activated carbon, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0159] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O and 0.125g Ba(NO3)2 in a beaker, add 20mL deionized water, and then immerse 5g activated carbon therein, immerse for 5h to obtain the product, and then dry it in a forced air drying oven at 110°C for 24h to obtain the product.
[0160] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0161] Comparative Example 4
[0162] Compared with Example 1, Comparative Example 5 differs in that the carrier is Al2O3, and the rest of the processing methods are exactly the same as those of Example 1.
[0163] Step 1: Al2O3 pretreatment: 10g Al2O3 was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated Al2O3. NH3-TPD was used to characterize the surface acidity of Al2O3. After alkali pretreatment, the NH3 desorption peak of Al2O3 at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0164] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to the treated Al2O3, let it stand for 2 hours, transfer it to a tube furnace, heat it to 350°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, and continue to heat it to 600°C and keep it for 4 hours. According to BET characterization analysis, the micropore ratio is 60% and the specific surface area is 200m 2 / g, the average pore size is 0.5nm, and the number of oxygen-containing groups on the surface is 0.8wt% (based on O content) as determined by VarioEL analyzer.
[0165] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O and 0.125g Ba(NO3)2 in a beaker, add 20mL deionized water, and then impregnate 5g Al2O3 therein, soak for 5h to obtain the product, and then dry it in a forced air drying oven at 110°C for 24h to obtain the product.
[0166] Step 4: Reduction and chlorination of active components: The product in step 3 was transferred to a tubular furnace and heated to 300°C at a rate of 1°C / min under a hydrogen-argon mixture (5% H2+95% Ar), maintained for 2 hours, then heated to 800°C at a rate of 1°C / min, maintained for 2 hours, and after cooling to room temperature, HCl gas was passed into it and maintained for 1 hour. Subsequently, the temperature was increased to 500°C at a rate of 1°C / min, maintained for 1 hour, and naturally cooled to room temperature.
[0167] Comparative Example 5
[0168] Compared with Example 1, Comparative Example 5 is different in that the active component is not reduced, and the rest of the treatment is exactly the same as that of Example 1.
[0169] Step 1: Activated carbon pretreatment: 10g activated carbon was added to 300mL 5wt% NH3·H2O solution and refluxed at 50℃ for 10h. After the reflux was completed, the temperature was cooled to room temperature, filtered with deionized water and washed with water until neutral, and dried at 100℃ for 24h to obtain pretreated activated carbon. NH3-TPD was used to characterize the surface acid properties of activated carbon. After alkali pretreatment, the NH3 desorption peak of activated carbon at low temperature increased significantly, that is, the number of weakly acidic sites increased.
[0170] Step 2: Removal of oxygen-containing groups: Add 20 mL of water to 10 g of activated carbon, let stand for 2 h, transfer to a tube furnace, heat to 350 ° C at a rate of 1 ° C / min in a nitrogen atmosphere, keep for 2 h, and continue to heat to 600 ° C and keep for 4 h. According to BET characterization analysis, the micropore ratio is 95% and the specific surface area is 940 m 2 / g, the average pore diameter is 1.5nm, and the number of oxygen-containing groups on the surface is 0.5wt% (based on O content) as determined by VarioEL analyzer.
[0171] Step 3: Loading of active components: Take 0.125g Zn(NO3)2·6H2O in a beaker, heat it to 50℃ to dissolve it, then dissolve 0.125g Ba(NO3)2 therein, and then impregnate 5g activated carbon therein, impregnate for 5h to obtain the product, and then freeze-dry it at -50℃ for 24h to obtain the product.
[0172] Step 4: Chlorination of active components: Move the product in step 3 to a tubular furnace and heat it to 300°C at a rate of 1°C / min under a nitrogen atmosphere, keep it for 2 hours, then heat it to 800°C at a rate of 1°C / min, keep it for 2 hours, and after it is cooled to room temperature, pass HCl gas into it and keep it for 1 hour. Subsequently, heat it to 500°C at a rate of 1°C / min, keep it for 1 hour, and naturally cool it to room temperature.
[0173] Embodiment 23
[0174] The catalysts of Examples 1-22 were respectively loaded into a fixed bed reactor, the reaction tube was 500 mm long and 40 mm in inner diameter, the amount of catalyst used in Examples 1-22 was 10.0 g, quartz wool was padded under the catalyst bed, quartz wool and quartz sand were padded on the upper end, the particle size ratio of the reaction tube to the catalyst was 15, and the reaction temperature was 230 ° C; after the temperature stabilized, nitrogen or argon was used as a carrier gas to bring the vaporized 1,1,2,2-tetrachloroethane into the reactor, the carrier gas flow rate was 30 mL / min, and the raw material feed space velocity was 10000 h -1 The product enters the gas-liquid separator after passing through the condensation device. The liquid product is collected and diluted after condensation and analyzed by Agilent gas chromatography. The gas product HCl is absorbed by alkaline solution. The reaction results are shown in Table 1.
[0175] Comparative Example 6
[0176] The reaction was carried out in a fixed bed reactor, the reaction tube was 500 mm long and 40 mm in inner diameter, the amount of catalyst used in Comparative Examples 1-5 was 10.0 g, quartz wool was padded under the catalyst bed, quartz wool and quartz sand were padded on the top, the particle size ratio of the reaction tube to the catalyst was 15, the reaction temperature was 230°C, and after the temperature was stabilized, nitrogen or argon was used as a carrier gas to bring the vaporized 1,1,2,2-tetrachloroethane into the reactor, the carrier gas flow rate was 30 mL / min, and the raw material feed space velocity was 10000 h -1 The product enters the gas-liquid separator after passing through the condensation device. The liquid product is collected and diluted after condensation and analyzed by Agilent gas chromatography. The gas product HCl is absorbed by alkaline solution. The reaction results are shown in Table 2.
[0177] Embodiment 24
[0178] Referring to the reaction conditions of Example 23, the reaction time was extended and the stability test of the catalyst of Example 4 was carried out. The reaction results are shown in Table 3.
[0179] Table 1. Catalytic performance results of catalysts prepared in Examples 1-22
[0180]
[0181]
[0182] Table 2. Catalytic performance results of catalysts prepared in Comparative Examples 1-5
[0183] Conversion rate / % Selectivity / % Comparative Example 1 86.2 93.5 Comparative Example 2 79.0 88.5 Comparative Example 3 92.0 92.5 Comparative Example 4 70.0 79.0 Comparative Example 5 88.5 94.5
[0184] Table 3. Catalyst stability test results of Example 24
[0185] Time / h Conversion rate / % Selectivity / % 5 99.9 99.0 10 99.9 98.9 50 99.9 99.0 100 99.9 99.5 200 99.7 98.7 500 99.6 98.9 700 99.6 98.6 1000 99.6 98.9
[0186] In summary, the present invention prepares an activated carbon-supported metal chloride high-efficiency catalyst by pretreating the activated carbon carrier, directly impregnating the active component with the activated carbon and freeze-drying the catalyst, which has good catalytic activity in the dehydrochlorination reaction of 1,1,2,2-tetrachloroethane to synthesize trichloroethylene, and prolongs the service life of the catalyst while maintaining high conversion and high selectivity.
Claims
1. A method for preparing a dehydrochlorination catalyst, characterized in that: The preparation method comprises the following steps: A1. Add activated carbon to 5-10wt% HNO3 solution or 5-10wt% NH3·H2O solution and reflux at a reflux temperature of 50-80°C for 5-10h; after reflux, wait for the temperature to drop to room temperature, filter with deionized water and wash to neutral, and dry to obtain pre-treated activated carbon; A2. Add a pore-forming agent to the activated carbon, let it stand for 2-6 hours, transfer it to a tube furnace, and heat it to 400-800°C at a rate of 1-10°C / min under an inert atmosphere, with a gas flow rate of 20-60mL / min, and maintain it for 2-8 hours; the pore-forming agent is one of water, polyethylene glycol, polyvinyl alcohol, and polyacrylamide, or a combination of water and any one of polyethylene glycol, polyvinyl alcohol, and polyacrylamide; A3. Prepare a metal salt aqueous solution, wherein the solute in the metal salt solution is one of Zn(NO3)2, Ba(NO3)2 and CsNO3 or a combination of Zn(NO3)2 and one of Ba(NO3)2 and CsNO3, add the activated carbon obtained in A2 thereto, and immerse at room temperature for 5-10 hours to obtain a product; then, freeze-dry to obtain a product; the mass ratio of the activated carbon to the metal salt is 10-40:1; A4. The product in A3 is placed in a tubular furnace, and a reducing gas containing hydrogen is introduced to reduce the metal salt to a metal element. The reduction conditions are: heating to 300-800°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and maintaining the temperature for 2-5h; then HCl gas is introduced to react with the metal element to generate a metal chloride. The reaction conditions are: introducing HCl gas at a gas flow rate of 20-60mL / min, and reacting at room temperature to 800°C for 0.1-3h, thereby obtaining a dehydrochlorination catalyst.
2. The preparation method according to claim 1, characterized in that: The activated carbon of step A1 is one of wood carbon and coconut shell carbon.
3. The preparation method according to claim 1, characterized in that: In step A1, the feed ratio of activated carbon to HNO3 solution or NH3·H2O solution is 1g:20-50mL.
4. The preparation method according to claim 1, characterized in that: In step A2, the mass ratio of activated carbon to pore-forming agent is 1:2-4.
5. The preparation method according to claim 1, characterized in that: The freeze-drying conditions in step A3 are: freeze-drying the impregnated product at -30 to -50°C for 20 to 30 hours.
6. The preparation method according to claim 1, characterized in that: In step A4, the reducing gas containing hydrogen is a H2 / Ar mixed gas, wherein the volume percentage content of hydrogen is 5-10%.
7. The preparation method according to claim 1, characterized in that: In step A4, the metal is Zn, and the reduction conditions are: heating to 300-400°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and keeping the temperature constant for 2-5h; or the metal is one of Ba and Cs3 or a combination of Zn and one of Ba and Cs, and the reduction conditions are: heating to 300-400°C at a rate of 1-10°C / min in a H2 / Ar mixed gas with a gas flow rate of 20-60mL / min, and keeping the temperature constant for 1-3h; then, heating to 400-800°C at a rate of 1-10°C / min, and keeping the temperature constant for 1-3h.
8. The preparation method according to claim 1, characterized in that: In step A4, the metal is Cs or a combination of Zn and Cs, and the reaction conditions for generating metal chloride are: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature, and maintaining for 0.1 to 3 hours; or the metal is Zn or a combination of Zn and Ba, and the reaction conditions for generating metal chloride are: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature, maintaining for 0.1 to 1 hour, and then heating to 400-800°C at a rate of 1-10°C / min, and then maintaining for 0.1-1 hour; or the metal is Ba, and the reaction conditions for generating metal chloride are: passing HCl gas at a gas flow rate of 20-60 mL / min at room temperature, heating to 400-800°C at a rate of 1-10°C / min, and then maintaining for 0.1-1 hour.
9. A dehydrochlorination catalyst prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the dehydrochlorination catalyst as claimed in claim 9 in the synthesis of 1,1,2-trichloroethylene from 1,1,2,2-tetrachloroethane.
Citation Information
Patent Citations
Catalyst for preparing perchloroethylene by catalyzing pentachloroethane to remove HCl and preparation method thereof
CN104001534A
Hydrodechlorination catalyst and process thereof
CN116037153A
Catalyst for dehydrochlorination of chloralkane to produce chloroalkene and its preparation method
CN1876238A
Method of producing trichloroethylene from tetrachloroethane
GB798451A
Method for dechlorinating / detoxifying organochlorine compound relatively easy to decompose mainly comprising monochloro-, dichloro-, trichloro-, tetrachloro-ethylenes, and the like
JP2004322065A
